Fermentation of soymilk by yoghurt and bifidobacteria strains - Šárka HORÁČKOVÁ; Andrea MÜHLHANSOVÁ; Marcela SLUKOVÁ; Věra SCHULZOVÁ; Milada PLOCKOVÁ (Czech Journal of Food Sciences, 2015)
Soy and milk based products fermented by yoghurt culture YC-381 alone or in combination with two probiotic cultures (Bifidobacterium animalis subsp. lactis BB 12 and Bifidobacterium bifidum CCDM 94) were prepared. Bacteria growth, the amounts of lactic acid, acetic acid, and acetaldehyde were compared after 16 h of fermentation at 37°C. The changes of isoflavones concentrations were also monitored in soy products. The growth of Streptococcus thermophilus and bifidobacteria was similar in both media, but Lactobacillus delbrueckii subsp. bulgaricus showed a better growth in milk. Titratable acidity and the concentrations of acids were consistently higher in cow milk than in soymilk at the end of fermentation. Bifidobacteria, compared to the yoghurt culture, were only able to acidify the media to the half values. Comparing the bifidobacteria strains, Bifidobacterium animalis subsp. lactis BB 12 exhibited a better ability to acidify milk. The strain Bifidobacterium bifidum CCDM 94 was able to release 6.90 mg/100 ml of isoflavone aglycones in soymilk.